The Effectiveness of the HEY Website for Increasing Adolescents’ Reproductive Health Knowledge - Nurmala, Ira; Agus Salim, Lutfi; Muthmainnah, Muthmainnah; Nadia, Asma; Suria Zainuddin; Sandra Pérez (Universitas Airlangga, 2025)
Background: Conventional health promotion media such as leaflets are considered not to meet the needs of patients for health information. Ineffective health promotion media can contribute to the occurrence of a health problem. The HEY Website is a health promotion media that is aligned with the current situation which is the digital era. Objectives: This study was conducted to analyze the increase in knowledge of high school students who have received edutainment interventions from the HEY Website. Methods: This research was quantitative research with a quasi-experimental research design in the form of peer educator training using the HEY website. The respondents of this study were 50 high school students at SMAN 1 Turen in Malang Regency with the inclusion criteria being grade X and XI and active in student organizations as they may bring better influence among peers. Results: There was an increase in knowledge, as shown by the average pretest score of 64.5. After the training, the post-test score showed an average number of 86.2. Statistical analysis also showed significant results in knowledge differences before and after the intervention (P=0,000). Conclusion: The HEY website as a digital-based adolescent health promotion media proved significant in increasing student knowledge about adolescent health.